Relationship between the amount of blood transfusion and the amount of iron chelation with blood and salivary ureum levels in children with beta thalassemia major - Pradypta, Putu Gyzca
Introduction: Patients with thalassemia experience a synthesis of one of the beta chains of the globin gene, resulting in reduced hemoglobin formation. Patients with beta-thalassemia major require routine transfusions and iron chelation. Both of these cause impaired kidney function. This study aims to determine the relationship between the amount of blood transfusion and the amount of iron chelation with blood urea and saliva levels in children with beta-thalassemia major.